The authority of inspectors of education: auctoritas and potestas - Camacho Prats, Alexandre; Rodríguez Bravo, Marcos Francisco (Avances en Supervisión Educativa, 2017)
Educational Inspection is an institution with almost 170 years of history that traditionally has enjoyed credibility and influence, endorsed by the knowhow and good works of its inspectors. Furthermore, from the mid twentieth century, these government workers legally boast the category of Public Authority. In this article we highlight the concepts of Auctoritas and Potestas, which describe the notion of authority of the Educational Inspectors and we carry out a theoretical revision of the current legislation by showing its impact in six Spanish Autonomous Communities. In addition, we examine scientific works by authors of reference. We can conclude that the legal authority does not necessarily implicate a moral authority, and in order for it to be reached, it appears necessary to obtain a solid training in Pedagogy by the Educational Inspectors, and at the same time a constant update in diverse fundamental elements of the scholastic actuality. In this work, we process the authority of the Inspector staff from a perspective that encourages the reflection on the profile that should characterize these public workers with their performances and interventions.